Hyperboles Used by A Beauty Influencer in The Beauty Product Reviews Videos on YouTube - Pulungan, Ulfa Julianti; Damanik, Sisila Fitriany (Universitas Negeri Medan, 2022)
This study attempts to analyze hyperboles used by a beauty influencer in the beauty product review videos on YouTube. One of the most famous beauty influencer named Suhay Salim in her beauty product reviews videos on her YouTube channel often applying hyperbolic utterances. By following Claridge (2011) and Cano Mora (2006) theory of hyperbole, the study aims to find out the form of hyperbole that used by Suhay Salim in her beauty product reviews videos, and also how the hyperbolic utterance conveyed and why they used in the ways they are. In order to achieve the aims, the data is in the form of utterances that was selected from two of Suhay Salim™s most popular videos which contain skincare products review on her YouTube channel. The study adopts descriptive qualitative research method in order to give detailed explanation in describing the phenomenon. The results show that Suhay Salim uses six forms of hyperbole such as single word, phrasal, clausal, numerical, comparison and repetition hyperbole. And they are conveyed through variations of words, phrases and clauses. There are found some hyperbolic markers which can be grouped into two hyperbole form. There are found more than one hyperbolic marker in one example. And there are also found some examples have the same hyperbolic utterance. Moreover, the use of the hyperbole makes the utterances during reviewing the products way more attractive, convincing and persuasive which can attracts the viewer™s attention and influence them to buy the same product as the reviewer.